Impact of Social Media on the Writing Abilities of Ambrose Alli University Undergraduates in Ekpoma-Nigeria - Omoera, Osakue Stevenson; Aiwuyo, Oluranti Mary; Edemode, John O; Anyanwu, Bibian O (GIST – Education and Learning Research Journal, 2018)
This article examines the impact of social media on the writing abilities of Nigerian youths in English, which is the language of mass communication in Nigeria. Deploying cultivation theory of the media, this study uses quantitative and qualitative methods to unpack the Nigerian youths’ opinions on the impact of the use of the new media of social networking platforms such as Facebook, WhatsApp, Instagram, etc., on their writing abilities, using undergraduates of Ambrose Alli University, Ekpoma-Nigeria as a study case. To do this, information is gathered through the use of 120 copies of a validated survey questionnaire. Additional information is garnered from in-depth interviews (IDIs) with lecturers from within and outside Ambrose Alli University and focused group discussion (FGD) with some students of the institution as well as the researchers’ direct observation of the issue under investigation. The study discovers that a majority of the youth adopt a certain option/brand of English which cannot be located within the matrixes of Standard English or even its Popular Nigerian English (PNE) variant which is called Pidgin English. Consequently, expressions such as ‘u’ for ‘you’ ‘gr8t’ for ‘great’, ‘ur/urs’ for ‘your/yours’, among other deviational patterns, have crept into their writing consciousness in classes and examinations, which make a lot of ‘sense’ in informal settings among the youths, but smacks of sub literacy in formal writing situations under which they are being trained. As well, shortened forms of words and phrases such ‘LOL’, ‘K,’ ‘IJNA,’ ‘Y’, etc., are common sights in their writings. This development can have serious implication for effective and efficient writing among Nigerian youths, especially in formal situations. The study suggests that because it has been demonstrated that effective and efficient writing can improve comprehension of content in any discipline, enabling students to practice analysis, synthesis, and other skills that constitute critical, creative, and even civic thinking, students should be encouraged to write effectively and efficiently as more writing equals more learning even in the age of the new media (social media). It advises that further studies should be carried out on the deviational patterns and shortened forms of English words and phrases which are commonly used by youths in Nigeria and elsewhere, with a view to possibly getting the ‘new words’ standardized by the relevant educational authorities to ensure uniformity in usage, and to keep pace with the dynamically trendy youth/social media culture.